A survey of hand hygiene knowledge, attitude and practices among health care workers in a tertiary hospital, Southwestern Nigeria - RD Agbana; SP Ogundeji; JS Owoseni (Archives of Community Medicine and Public Health - Peertechz Publications, 2020)
Background: Improper hand hygiene practices among Healthcare Providers (HCPs) are a common risk factor for and interventions to improve hygiene have proven to be effective strategy in reducing nosocomial infection. Hand hygiene has been described as the single most important, simplest and least expensive means of preventing nosocomial infections.  Aim/Objectives: The studied was carried out to determine the knowledge, attitude and practice of hand hygiene among healthcare workers in a tertiary health facility.    Materials/Methods: A cross- sectional study was conducted among 368 doctors, nurses and ward attendants using multistage sampling technique.  Data were collected with a set of self- administered, modified WHO questionnaire and  analyzed using IBM and SPSS version 25 statistical package. Results: The mean age of respondents was 35.2±9.3 years, and majority of them were between 36-45years (33.6%). The male to female ratio was 1.6: 1.  Most of the respondents were nurses (41.5%) and  370 (98.95%) of the respondents had a good knowledge of hand hygiene. Washing of hands before and after contact with patients was 44.65% and 56.2% respectively. Most of them have received training on hand washing in the last three years (53.4%), 222 (62.7%) respondents routinely used alcohol based hand rub. The main reason cited for not observing hand hygiene practices consistently were lack of running water (53.4%), unavailability of  alcohol based hand rub(26.6%), and dirty water sinks (24.0%).  Conclusion: Although knowledge, attitude and practice of hand hygiene were good among respondents in this study, lack of running water and unavailability of alcohol based hand rub remain major constraints.  Hospital management should therefore provide adequate water supply and materials for sanitation and hand hygiene in healthcare facilities.